2001
DOI: 10.1046/j.1469-8137.2001.00121.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of Catharanthus roseus (periwinkle) to ash yellows phytoplasmal infection

Abstract: Summary• Photosynthetic responses of periwinkle ( Catharanthus roseus ) were compared during disease development after infection by two strains of ash yellows (AshY) phytoplasmas that differed in aggressiveness.• Healthy plants were inoculated by grafting with diseased scions. Mature leaves formed before grafting of diseased scion, and leaves formed during disease development were monitored for physiological changes.• Leaves formed before inoculation remained visually and physiologically asymptomatic until nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 56 publications
4
17
0
Order By: Relevance
“…Therefore, it is more likely that the phytoplasma infection-induced alteration in hormonal signaling triggers reprogramming of the plant growth and developmental pattern, leading to some symptoms in infected plants. This is in accord with early reports that phytoplasma infection disturbs hormonal balance in the host plants433343536.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, it is more likely that the phytoplasma infection-induced alteration in hormonal signaling triggers reprogramming of the plant growth and developmental pattern, leading to some symptoms in infected plants. This is in accord with early reports that phytoplasma infection disturbs hormonal balance in the host plants433343536.…”
Section: Discussionsupporting
confidence: 92%
“…These may explain the different results in the expression patterns of some genes obtained by AFLP and qRT-PCR. As reported by Tan and Whitlow (2001), leaves formed before inoculation remained visually and physiologically asymptomatic, this phenomenon can also explain the differences obtained in this research for the gene expression patterns between symptomatic and nonsymptomatic samples.…”
Section: Discussionsupporting
confidence: 50%
“…In addition, subsequent blocks in sugar and protein translocation are followed by an increase of starch in source leaves and a decrease in sink leaves and roots as previously observed in coconut palms affected by lethal yellowing (Maust et al, 2003) and in maize plants affected by bushy stunt (Junqueira et al, 2004). Additionally, a related decrease in chlorophyll content and chlorophyll biosynthesis has been observed in coconut palms affected by coconut lethal yellowing (Leon et al, 1996), in apple trees affected by apple proliferation (Bertamini et al, 2002a) and periwinkles affected by ash yellows (Tan & Whitlow, 2001).…”
Section: Introductionsupporting
confidence: 59%
“…Currently, the key ecophysiological leaf traits related to phytoplasma disease symptoms are decreased rates of gas exchange variables: carbon assimilation (A) and water transpiration (E) (Tan & Whitlow, 2001;Endeshaw et al, 2012). Proposed mechanisms leading to stomatal closure were related to an increase in abscisic acid (ABA) concentration (Leon et al, 1996;Martinez et al, 2000) and sucrose accumulation around guard cells, as reported by Lu et al (1997).…”
Section: Introductionmentioning
confidence: 96%